Analisis Efektivitas Organisasi Pada Badan Pusat Statistik Kota Dumai - Tamara Indah Natalia; Sufian Hamim; Dia Meirina Suri; Raden Imam Al Hafis (Journal of Innovative and Creativity (Joecy), 2026)
This study examines organizational effectiveness at the Central Statistics Agency (Badan Pusat Statistik/BPS) of Dumai Municipality, a vertical government institution responsible for producing official statistics at the city level. As a small unit with only twenty-four employees serving an entire municipality comprising seven districts, BPS Dumai faces a structural tension between an expanding statistical mandate and limited human resources. This research aims to describe and analyze the organization's effectiveness through five dimensions developed by Steers (1985) and Gibson, Ivancevich, and Donnelly (2011): production, efficiency, employee satisfaction, adaptability, and development. A descriptive qualitative method with a case-study design was applied, relying on documentary analysis of the agency's official Performance Accountability Report for fiscal year 2023, its 2020-2024 Strategic Plan, and its annual Performance Agreement, interpreted through the interactive analysis model of Miles, Huberman, and Saldana (2014). The findings indicate that BPS Dumai achieved an overall performance attainment of 100.34 percent in 2023, with budget absorption reaching 99.25 percent and the best Budget Execution Quality Index among all BPS units in Riau Province. However, beneath these formal indicators lie persistent vulnerabilities: heavy reliance on a small permanent workforce, declining respondent cooperation in data collection, fragmented data-processing systems, and the absence of competency-based workforce planning. The study concludes that organizational effectiveness in a statistical vertical agency cannot be inferred solely from quantitative output achievement, but must also account for adaptive capacity and human-resource sustainability as preconditions for long-term institutional resilience.